2006
DOI: 10.1029/2005jc003158
|View full text |Cite
|
Sign up to set email alerts
|

Whitecap coverage from satellite measurements: A first step toward modeling the variability of oceanic whitecaps

Abstract: [1] We present estimates of whitecap coverage on a global scale from satellite-measured brightness temperature of the ocean surface. This is a first step in a larger framework aiming at more realistic modeling of the high variability of whitecap coverage as a function of wind speed and a suite of additional environmental and meteorological factors. The involvement of oceanic whitecaps in various physical and chemical processes important for climate studies such as production of sea-salt aerosols, enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
199
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 189 publications
(220 citation statements)
references
References 138 publications
8
199
2
Order By: Relevance
“…More than a dozen empirical models as a function of wind speed have been proposed so far. However, they exhibit great discrepancies as reported by Anguelova and Webster (2006). Recent studies indicated that the whitecap coverage is influenced by the state of the wind wave development.…”
Section: Model Of Gas-transfer Velocity In the Presence Of Wave Breakingmentioning
confidence: 46%
“…More than a dozen empirical models as a function of wind speed have been proposed so far. However, they exhibit great discrepancies as reported by Anguelova and Webster (2006). Recent studies indicated that the whitecap coverage is influenced by the state of the wind wave development.…”
Section: Model Of Gas-transfer Velocity In the Presence Of Wave Breakingmentioning
confidence: 46%
“…(3), are implicitly based on the assumption that the local sea state is directly related to the local wind speed. However, satellite observations of whitecap coverage give evidence that the local sea state is determined by factors other than just wind speed (Anguelova and Webster, 2006). In particular, the observed whitecap coverage in tropics is higher than would be expected based on the wind speed.…”
Section: Comparison With Observationsmentioning
confidence: 90%
“…Monahan (1985, in Monahan andO'Muircheartaigh, 1986) showed that the time constant characterizing the decay of whitecaps changed inversely with the terminal rise speed of the smaller bubbles. Anguelova et al (2006) stated that a decrease in viscosity caused by higher water temperatures facilitated wave breaking and as a consequence prolongs the lifetime of a whitecap. Another suggested explanation for observed large-scale increases in whitecap fraction with an increase in water temperature is the difference in the duration of a certain wind speed over different areas.…”
Section: Effect Of Sea Water Temperature On Particle Number Concentramentioning
confidence: 99%